Aerobiology of the Wheat Blast Pathogen: Inoculum Monitoring and Detection of Fungicide Resistance Alleles - Vicentini, Samara Nunes Campos [UNESP]; Hawkins, Nichola J.; King, Kevin M.; Moreira, Silvino Intra [UNESP]; de Paiva Custódio, Adriano Augusto; Leite Júnior, Rui Pereira; Portalanza, Diego; Garcés-Fiallos, Felipe Rafael; Krug, Loane Dantas [UNESP]; West, Jonathan S.; Fraaije, Bart A.; De Jesus Júnior, Waldir Cintra; et al. (MDPI, 2023)
Wheat blast, caused by the ascomycetous fungus Pyricularia oryzae Triticum lineage (PoTl), is mainly controlled by fungicide use, but resistance to the main fungicide groups—sterol demethylase (DMI), quinone outside (QoI), and succinate dehydrogenase inhibitors (SDHI)—has been reported in Brazil. In order to rationalize fungicide inputs (e.g., choice, timing, dose-rate, spray number, and mixing/alternation) for managing wheat blast, we describe a new monitoring tool, enabling the quantitative measurement of pathogen’s inoculum levels and detection of fungicide resistance alleles. Wheat blast airborne spores (aerosol populations) were monitored at Londrina in Paraná State, a major wheat cropping region in Brazil, using an automated high-volume cyclone coupled with a lab-based quantitative real-time PCR (qPCR) assay. The objectives of our study were as follows: (1) to monitor the amount of PoTl airborne conidia during 2019–2021 based on DNA detection, (2) to reveal the prevalence of QoI resistant (QoI-R) cytochrome b alleles in aerosol populations of wheat blast, and (3) to determine the impact of weather on the dynamics of wheat blast aerosol populations and spread of QoI resistant alleles. PoTl inoculum was consistently detected in aerosols during the wheat cropping seasons from 2019 to 2021, but amounts varied significantly between seasons, with highest amounts detected in 2019. High peaks of PoTl DNA were also continuously detected during the off-season in 2020 and 2021. The prevalence of QoI resistant (QoI-R) cytochrome b G143A alleles in aerosol populations was also determined for a subset of 10 PoTl positive DNA samples with frequencies varying between 10 and 91% using a combination of PCR-amplification and SNP detection pyrosequencing. Statistically significant but low correlations were found between the levels of pathogen and the weather variables. In conclusion, for wheat blast, this system provided prior detection of airborne spore levels of the pathogen and of the prevalence of fungicide resistance alleles.
Keywords: airborne spores; epidemic predictors; integrated disease management; Pyricularia oryzae Triticum lineage